A cross-country analysis on diversification, Sukuk investment, and the performance of Islamic banking systems under the COVID-19 pandemic - Le TDQ; Ho TH; Nguyen DT; Ngo T (Elsevier Ltd, 2022)
This study investigates the relationship between diversification and Islamic banking systems' performance under the impact of the COVID-19 turmoil using a sample of 24 countries from 2013Q4 and 2020Q4. The findings indicate that the performance of Islamic banking systems is positively associated with sectoral diversification of Shari'ah-compliant financing and income diversification. Although this study confirms a negative impact of the COVID-19 shock, income diversification is found to mitigate the adverse effect of this health crisis on the performance of the Islamic banking systems. In which, Sukuk investment is considered an essential channel for pursuing this diversification strategy. Therefore, this research has important implications for policymakers, managers, and academics.
Keywords: COVID-19; Diversification; Generalized method of moments (GMM); Islamic banking systems; Performance; Sukuk investment